Publicização da educação especial no Paraná: gestão Requião (2003-2010) - Moraes, Valdete Aparecida Veiga de (2011)
This work, related to the Research Area of Education Public Policies, of the Universidade Tuiuti do Paraná, has as subject the Publicization of Special Education in Paraná – During the Government Years of Requião (2003 through 2010). In Paraná, the non-profit philanthropic entities are responsible for the provision of the services offered in special schools, with respect to the education services to intellectually disabled students. These entities are hegemonic, exercise a great influence in the direction off the public policy regarding Special Education, receiving, further, financial aid to finance its activities in the area. The public policies, on their turn, are strengthened by the publicization speech from the Education services. In the scope of this publicization, the services offered by the Special Education became a benefit guaranteed by the State. In view of the orientation of the neoliberal ideology following such policies, it can be verified that they tend to comply with the market laws. In face of the above, it is vital for us to query: to which extent does the publicization of the Special Education in Paraná contributes to extinguish the inequalities historically constituting the education of people intellectually disabled? Who benefits from this Reform of the State and in Education? Which are the bases to such Reform? With the intention of answering to these matters, the investigation proposed herein has as general object to analyze the Special Education Policies in the State of Paraná beginning on the Government Years of Requião (2003-2010) in light of the analysis of the socio-economic and ethical-political relations established based on national and foreign trends of educational inclusion. It is, therefore, elected the idea of "hegemony", as understood based on the thinking of Antonio Gramsci, as the main theoretical category on which the investigation carried out hereby will be based. And, in this category we will look for basis to understand the contradictions existent at the relationships established for the maintenance of the capitalist society. The research was carried out by means of the analysis of documents from sources representative in the Special Education policy in the State of Paraná in the period considered. This policy consists in the maintenance of the special schools in cooperation with the third sector by means of management agreements. The decision of the best pedagogic organization, with the purpose of human formation of the intellectually or mental disabled person, depends on a broad national debate. That is, depends on the promotion of discussions capable of assisting the population and families of these students to become more critical and capable of claiming the effective participation of the State.